UMPSA and CLSU celebrate COAR 2025 focusing on knowledge sharing in Biotechnology and Agriculture - Nor Hasmaliana, Abdul Manas; Aishah, Mohd Marsin (UMPSA, 2025)
GAMBANG, 17 June 2025 - The Faculty of Industrial Science and Technology (FIST), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has successfully organized the 5th Academic and Research Colloquium (COAR 2025) in collaboration with the College of Fisheries, Central Luzon State University (CLSU), Philippines.